Single crystal aluminum nitride powder surface fluidization modification method

By using fluidized bed technology to form a covalent bonded alumina protective layer on the surface of single crystal AlN powder, the problem of difficulty in improving mechanical strength and thermal conductivity in the prior art is solved, and uniform coating and thickness of the material are achieved Control significantly improves performance stability.

CN119433504AActive Publication Date: 2025-02-14UNIV OF SCI & TECH BEIJING
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411583020.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

In the prior art, the surface modification of single crystal AlN powder is mainly used to prepare hydrophobic coatings to resist hydrolysis, which fails to effectively improve the mechanical strength and thermal conductivity of aluminum nitride fillers, and the thickness uniformity and stability of the modified coating. Difficult to control.

Method used

Fluidized bed technology is used to form a stable covalent bonded alumina protective layer on the surface of single crystal AlN powder, which achieves uniform deposition and strong chemical bonding through chemical reactions, improving adhesion and durability.

Benefits of technology

The uniform coating and thickness control of the surface of single crystal AlN powder is achieved, which significantly improves the mechanical strength, thermal conductivity and stability of the material, and enhances the performance in high temperature and extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433504A_ABST
    Figure CN119433504A_ABST
Patent Text Reader

Abstract

The invention provides a single-crystal aluminum nitride powder surface fluidization modification method, and relates to the technical field of single-crystal AlN powder surface modification technologies. The single-crystal aluminum nitride powder surface fluidization modification method comprises the steps of single-crystal AlN powder surface pretreatment, drying treatment, single-crystal AlN powder surface modification treatment and repeated and cyclic surface modification treatment, and single-crystal AlN powder coated with an aluminum oxide protection layer is obtained. According to the method, uniform coating and thickness control on the surface of the single crystal AlN powder can be realized through a fluidization modification technology, and the modified single crystal AlN powder capable of enhancing the hydrolysis resistance, the heat-conducting property, the interfacial compatibility and other properties of the aluminum nitride filler can be obtained; the method is simple and easy to operate, reduces dependence on harmful solvents, is green and environment-friendly, is low in cost and high in efficiency, and is beneficial to industrial large-scale production and popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface modification technology of single crystal AlN powder, in particular to a surface fluidization modification method of single crystal aluminum nitride powder. Background Art

[0002] Aluminum nitride (AlN) has excellent thermal conductivity, electrical insulation and chemical stability, and is widely used in electronic devices, thermal management and ceramic matrix composites. However, the surface properties of AlN usually affect its dispersibility and interface bonding performance in composite materials, thus limiting its further application. Therefore, surface modification of AlN powder becomes the key to improving its performance.

[0003] Traditional surface modification methods, such as physical adsorption, coating or chemical deposition, often have the following shortcomings: 1) Insufficient adhesion. The coatings formed by many methods have weak bonding with the aluminum nitride surface and are easily detached during subsequent processing, resulting in performance degradation; 2) Uneven thickness. Traditional modification technologies make it difficult to achieve uniform coating thickness on the powder surface, affecting the consistency and reliability of the material; 3) Harsh reaction conditions. Some modification methods require high temperatures or complex reaction conditions, which increases production costs and energy consumption.

[0004] For example, Chinese patent CN112250047A discloses a method for hydrolysis resistance modification of aluminum nitride powder, in which an inorganic shell layer is first formed on the surface of aluminum nitride by a sol-gel method to coat the surface of aluminum nitride, and then organic matter is modified; obviously, the modification method is limited to hydrophobic properties, and although the formed inner shell of the inorganic component and the outer shell of the organic component both have this property, they do not have a uniform shell thickness.

[0005] Chinese patent CN112919432A discloses aluminum nitride powder and its modified preparation method. The method modifies the surface of aluminum nitride powder by organic solvent, so that AHP forms a protective layer on the powder surface to isolate it from water and prevent hydrolysis reaction. The protective layer makes the surfaces of the modified aluminum nitride powder adhere to each other, resulting in poor dispersibility, poor mechanical strength, hardness and other properties.

[0006] Chinese patent CN113772638A discloses a method for preparing a high-temperature oxidation-resistant aluminum nitride and aluminum oxide thermal conductive filler, which method requires first preparing an aluminum oxide solution, then reacting with an AlN solution under the action of different binders, and fixing it in the form of an AlN·Al2O3 precursor, and finally calcining the obtained precursor powder at a high temperature under the protection of an inert gas; it is obvious that the composition of the thermal conductive filler is Al2O3 wrapped on the surface of AlN, the distribution of the Al2O3 particles in the wrapping layer is not uniform, the surface is uneven, and the sharp protrusions are very obvious. Summary of the invention

[0007] In order to solve the problem that the surface of single-crystal AlN powder in the prior art is generally modified to prepare a hydrophobic coating to resist hydrolysis, it does not consider that the modification is to enhance the mechanical strength of aluminum nitride filler, improve its thermal conductivity, filling limit, compression, tension and bending resistance, and does not consider the technical problem that the thickness uniformity, thickness control, durability, stability and other properties of the modified coating are difficult to control; therefore, the present invention proposes a fluidized modification method for the surface of single-crystal aluminum nitride powder to form a stable covalently bonded alumina protective layer on the surface of single-crystal AlN powder. This method utilizes fluidized bed technology, can achieve uniform deposition under controllable conditions, and forms strong and firm covalent bonding through chemical reactions, significantly improving the adhesion and durability of the protective layer. The technical scheme is as follows:

[0008] A method for modifying the surface of a single-crystal aluminum nitride powder by fluidization, the method comprising the following steps:

[0009] S1. Surface pretreatment of single crystal AlN powder: weigh an appropriate amount of high-purity single crystal AlN powder, mix the single crystal AlN powder with anhydrous ethanol to prepare an AlN suspension, place the suspension in an ultrasonic cleaning machine and start a cleaning process while ultrasonicating and stirring, and then perform vacuum filtration to obtain AlN filler wet powder;

[0010] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment to obtain a single crystal AlN powder with a clean surface;

[0011] S3, surface modification of single crystal AlN powder: placing the cleaned single crystal AlN powder in S2 in a fluidized bed reactor, turning on a heating device to control the required fluidization temperature, introducing an alumina precursor into the fluidized bed reactor by spraying and reacting under an inert atmosphere, and then introducing an oxygen source into the fluidized bed reactor through a gas input system to carry out a surface covalent bonding reaction of the single crystal AlN powder under an inert atmosphere, thereby obtaining surface-modified single crystal AlN powder;

[0012] S4, repeat and cycle S3: repeat the surface modification treatment of S3 on the surface modified single crystal AlN powder of S3, forming an alumina protective layer with different thicknesses, uniform distribution and stable performance on the surface of the single crystal AlN powder, and obtaining a single crystal AlN powder coated with an alumina protective layer.

[0013] Optionally, the single crystal AlN powder in S1 has a particle size of 1-20 μm and a purity of 99.90-99.99%.

[0014] Optionally, the mass ratio of the single crystal AlN powder to anhydrous ethanol in S1 is 1:(1.58-4.74).

[0015] Optionally, the ultrasonic parameters of the cleaning process in S1 are set as follows: ultrasonic temperature 25-35° C., ultrasonic time 10-20 min.

[0016] Optionally, the drying temperature in S2 is 50-75° C., the drying time is 2-4 hours, and the surface-cleaned single crystal AlN powder is spherical or quasi-spherical in shape, with a particle size of 1-20 μm and a water content of 0.05-0.2%.

[0017] Optionally, the aluminum oxide precursor in S3 is at least one of trimethylaluminum, aluminum triacetylacetonate and aluminum chloride, and the flow rate of the aluminum oxide precursor is 0.3-1 L / min, and the time is 3-6 min.

[0018] Optionally, the oxygen source in S3 is at least one of oxygen, ozone and water (H2O), and the oxygen source is introduced at a flow rate of 0.3-1 L / min for 3-6 min.

[0019] Optionally, the inert atmosphere in S3 is at least one of nitrogen and argon, the time of inert gas introduction lasts from the beginning to the end of fluidization, and the flow rate of inert gas introduction is 0.2-2L / min; the fluidization treatment temperature is 120-300°C, and the fluidization time is 80-500min.

[0020] Optionally, in S3, the alumina precursor and the oxygen source are successively introduced into the fluidized bed reactor through different independent delivery systems.

[0021] Optionally, the number of cycles mentioned in S4 is 10-40, and the thickness of the aluminum oxide protective layer is controlled at 2-8nm; after a hydrolysis test at 80℃ / 72h, the pH fluctuation value of the fluidized modified aluminum nitride single crystal powder is 0-1, and the pH fluctuation value of the unmodified aluminum nitride single crystal powder is 2-6; the thermal conductivity of the fluidized modified aluminum nitride single crystal powder is improved by 10-30% compared with the unmodified one; under the same filling conditions, the unmodified filling limit is 75-80vol%, and the modified filling limit is increased to 88-95vol%.

[0022] Compared with the prior art, the above technical solution has at least the following beneficial effects:

[0023] The above scheme, the present invention proposes a fluidized modification method for the surface of single-crystal aluminum nitride powder, which can solve the problem that the surface of single-crystal AlN powder in the prior art is generally modified to prepare a hydrophobic coating to resist hydrolysis, but does not consider that the modification is to enhance the mechanical strength of the aluminum nitride filler, improve its thermal conductivity, filling limit, compression resistance, tensile strength and bending resistance, and does not consider the technical problem that the thickness uniformity, thickness control, durability, stability and other properties of the modified coating are difficult to control.

[0024] The present invention can achieve uniform coating and thickness control on the surface of single crystal AlN powder through fluidization modification technology, ensuring that each particle can obtain an aluminum oxide protective layer with uniform thickness uniformly distributed by aluminum oxide particles, thereby improving the overall performance of the material.

[0025] The fluidized modification technology of the present invention can ensure the formation of a strong chemical bond between the aluminum oxide layer and the single crystal AlN powder by covalent bonding, which not only improves the adhesion between the two, but also improves the overall durability and performance stability of the filler.

[0026] The aluminum oxide layer with uniform thickness and uniform particle distribution of the present invention can improve the thermal stability and chemical stability of single crystal AlN powder under high temperature conditions, so that it performs better in extreme environments.

[0027] The present invention can flexibly and accurately control the thickness and properties of the aluminum oxide layer by adjusting the process parameters in the fluidized modification process to meet different industrial application requirements.

[0028] The present invention obtains modified single crystal AlN powder by modifying the surface of single crystal AlN powder, which can enhance the hydrolysis resistance, thermal conductivity, interface compatibility and other properties of aluminum nitride single crystal powder, thus broadening the application scope and improving the use value.

[0029] In summary, compared with other traditional methods, the method of the present invention can achieve uniform coating and thickness control on the surface of single crystal AlN powder through fluidized modification technology, and can obtain modified single crystal AlN powder that can enhance the mechanical strength, compressive strength, tensile strength and flexural strength of aluminum nitride filler; the method is simple and easy to operate, reduces dependence on harmful solvents, is green and environmentally friendly, has low cost and high efficiency, and is conducive to large-scale industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 This is a process flow chart of a single crystal aluminum nitride powder surface fluidization modification method of the present invention;

[0032] Figure 2 This is a TEM image of a single crystal AlN powder coated with an aluminum oxide protective layer prepared by a single crystal aluminum nitride powder surface fluidization modification method according to Example 1 of the present invention;

[0033] Figure 3This is a TEM image of a single crystal AlN powder coated with an aluminum oxide protective layer prepared by a single crystal aluminum nitride powder surface fluidization modification method according to Example 2 of the present invention;

[0034] Figure 4 This is a TEM image of a single crystal AlN powder coated with an aluminum oxide protective layer prepared by a single crystal aluminum nitride powder surface fluidization modification method according to Example 3 of the present invention;

[0035] Figure 5 This is a TEM image of a single crystal AlN powder coated with an aluminum oxide protective layer prepared by a single crystal aluminum nitride powder surface fluidization modification method according to Example 4 of the present invention;

[0036] Figure 6 This is a TEM image of a single crystal AlN powder coated with an aluminum oxide protective layer prepared by a single crystal aluminum nitride powder surface fluidization modification method according to Example 5 of the present invention;

[0037] Figure 7 This is a TEM image of a single crystal AlN powder coated with an alumina protective layer prepared by a single crystal aluminum nitride powder surface fluidization modification method according to Example 6 of the present invention. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is described below in conjunction with the accompanying drawings.

[0039] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.

[0040] In the embodiments of the present invention, "image" and "picture" may sometimes be used interchangeably. It should be noted that when the distinction between them is not emphasized, the meanings they intend to express are consistent.

[0041] In the embodiments of the present invention, sometimes a subscript such as W1 may be written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are the same.

[0042] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0043] A single crystal aluminum nitride powder surface fluidization modification method, the single crystal aluminum nitride powder surface fluidization modification method is combined with Figure 1 Follow these steps:

[0044] S1. Surface pretreatment of single crystal AlN powder: weigh an appropriate amount of high-purity single crystal AlN powder, mix the single crystal AlN powder with anhydrous ethanol to prepare an AlN suspension, place the suspension in an ultrasonic cleaning machine and start a cleaning process while ultrasonicating and stirring, and then perform vacuum filtration to obtain AlN filler wet powder;

[0045] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment to obtain a single crystal AlN powder with a clean surface;

[0046] S3, surface modification of single crystal AlN powder: placing the cleaned single crystal AlN powder in S2 in a fluidized bed reactor, turning on a heating device to control the required fluidization temperature, introducing an alumina precursor into the fluidized bed reactor by spraying and reacting under an inert atmosphere, and then introducing an oxygen source into the fluidized bed reactor through a gas input system to carry out a surface covalent bonding reaction of the single crystal AlN powder under an inert atmosphere, thereby obtaining surface-modified single crystal AlN powder;

[0047] S4, repeat and cycle S3: repeat the surface modification treatment of S3 on the surface modified single crystal AlN powder of S3, forming an alumina protective layer with different thicknesses, uniform distribution and stable performance on the surface of the single crystal AlN powder, and obtaining a single crystal AlN powder coated with an alumina protective layer.

[0048] In particular, the particle size of the single crystal AlN powder in S1 is 1-20 μm; the purity is 99.90-99.99%.

[0049] In particular, the mass ratio of single crystal AlN powder to anhydrous ethanol in S1 is 1:(1.58-4.74).

[0050] In particular, the ultrasonic parameters of the cleaning process in S1 are set as follows: ultrasonic temperature 25-35° C., and ultrasonic duration 10-20 min.

[0051] In particular, the drying temperature in S2 is 50-75°C, the drying time is 2-4 hours, and the single crystal AlN powder with clean surface is spherical or quasi-spherical in shape, with a particle size of 1-20 μm and a water content of 0.05-0.2%.

[0052] Particularly, the aluminum oxide precursor in S3 is at least one of trimethylaluminum, aluminum triacetylacetonate and aluminum chloride, and the flow rate of the aluminum oxide precursor is 0.3-1 L / min, and the time is 3-6 min.

[0053] In particular, the oxygen source in S3 is at least one of oxygen, ozone and water (H2O), and the oxygen source is introduced at a flow rate of 0.3-1 L / min for 3-6 min.

[0054] In particular, the inert atmosphere in S3 is at least one of nitrogen and argon, the time of inert gas introduction lasts from the beginning to the end of fluidization, and the flow rate of inert gas introduction is 0.2-2L / min; the fluidization treatment temperature is 120-300°C, and the fluidization time is 80-500min.

[0055] In particular, the alumina precursor and the oxygen source in S3 are successively introduced into the fluidized bed reactor through different independent delivery systems.

[0056] In particular, the number of cycles mentioned in S4 is 10-40, and the thickness of the alumina protective layer is controlled at 2-8nm; after a hydrolysis test at 80℃ / 72h, the pH fluctuation value of the fluidized aluminum nitride single crystal powder is 0-1, and the pH fluctuation value of the unmodified aluminum nitride single crystal powder is 2-6; the thermal conductivity of the fluidized aluminum nitride single crystal powder is improved by 10-30% compared with the unmodified one; the interface compatibility between the fluidized aluminum nitride single crystal powder and the organic matrix is ​​improved, and under the same filling conditions, the filling limit of the unmodified one is 80vol%, and the filling limit of the modified one is increased to 90vol%.

[0057] Example 1

[0058] A method for modifying the surface of a single-crystal aluminum nitride powder by fluidization, the method comprising the following steps:

[0059] S1. Surface pretreatment of single crystal AlN powder: weigh 1 kg of single crystal AlN powder with a purity of 99.90% and a particle size of 1 μm, mix the single crystal AlN powder and anhydrous ethanol in a mass ratio of 1:2 to form an AlN suspension, place the suspension in an ultrasonic cleaning machine and start ultrasonic cleaning while stirring, the ultrasonic temperature is 30°C, the ultrasonic time is 10 min, and then vacuum filtration is performed to obtain AlN filler wet powder;

[0060] S2, drying treatment: the wet powder of AlN filler in S1 is placed in a drying oven for drying treatment, the drying temperature is 60°C, the time is 2 hours, and a single crystal AlN powder with a clean surface is obtained; the surface shape is spherical or quasi-spherical, the particle size is 1 μm, and the water content is 0.2%;

[0061] S3, surface modification of single crystal AlN powder: the cleaned single crystal AlN powder in S2 is placed in a fluidized bed reactor; the heating device is turned on to control the required fluidization temperature of 150°C, trimethylaluminum is introduced into the fluidized bed reactor by spraying and reacted in a nitrogen atmosphere, the flow rate of which is 0.5L / min, and the time is 5min; then oxygen is introduced into the fluidized bed reactor through a gas input system to carry out surface covalent bonding reaction of the single crystal AlN powder in a nitrogen environment, the flow rate of oxygen introduced into the fluidized bed reactor is 0.4L / min, the time is 5min, the flow rate of nitrogen introduced is 2L / min, the fluidization treatment temperature is 150°C, the fluidization time is 210min, and surface modified single crystal AlN powder is obtained; wherein: the alumina precursor and the oxygen source are successively introduced into the fluidized bed reactor through different independent conveying systems;

[0062] S4, repeat and cycle S3: repeat the surface modification treatment of the single crystal AlN powder of S3, the number of cycles is 20, the whole fluidization process duration is 210min, and a 4mm thick, uniformly distributed, stable performance alumina protective layer is formed on the surface of the single crystal AlN powder to obtain a single crystal AlN powder coated with an alumina protective layer.

[0063] The thickness of the aluminum oxide protective layer prepared in this embodiment is controlled at 4 nm. Figure 2 As shown, the hydrolysis resistance of the aluminum nitride single crystal powder after fluidization modification is significantly improved compared with that of the unmodified one. After the 80℃ / 72h hydrolysis test, the pH fluctuation value of the aluminum nitride single crystal powder after fluidization modification was 0.5-1, and the pH fluctuation value of the unmodified aluminum nitride single crystal powder was 2-6. The thermal conductivity of the fluidized aluminum nitride single crystal powder was improved by 10% compared with that of the unmodified one. The interfacial compatibility of the fluidized aluminum nitride single crystal powder and the organic matrix was improved. Under the same filling conditions, the filling limit of the unmodified one was 75vol%, and the filling limit of the modified one was increased to 88%.

[0064] Example 2

[0065] A method for modifying the surface of a single-crystal aluminum nitride powder by fluidization, the method comprising the following steps:

[0066] S1. Surface pretreatment of single crystal AlN powder: weigh 1 kg of single crystal AlN powder with a purity of 99.99% and a particle size of 3 μm, mix the single crystal AlN powder and anhydrous ethanol in a mass ratio of 1:1.6 to form an AlN suspension, place the suspension in an ultrasonic cleaning machine and start ultrasonic cleaning while stirring, the ultrasonic temperature is 30°C, the ultrasonic time is 10 min, and then vacuum filtration is performed to obtain AlN filler wet powder;

[0067] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment at a temperature of 50°C for 3 hours to obtain a single crystal AlN powder with a clean surface; the single crystal AlN powder with a clean surface is spherical or quasi-spherical in shape, with a particle size of 3 μm and a water content of 0.17%;

[0068] S3, surface modification of single crystal AlN powder: the single crystal AlN powder with cleaned surface in S2 is placed in a fluidized bed reactor; the heating device is turned on to control the required fluidization temperature of 150°C, aluminum chloride is introduced into the fluidized bed reactor by spraying and reacted in a nitrogen atmosphere, the flow rate of which is 0.3L / min, and the time is 3min; then oxygen is introduced into the fluidized bed reactor through a gas input system to carry out surface covalent bonding reaction of the single crystal AlN powder in a nitrogen environment, the flow rate of oxygen introduced into the fluidized bed reactor is 0.3L / min, the time is 3min, the flow rate of nitrogen introduced is 1.6L / min, the fluidization treatment temperature is 200°C, the fluidization time is 130min, and surface modified single crystal AlN powder is obtained; wherein: the aluminum oxide precursor and the oxygen source are successively introduced into the fluidized bed reactor through different independent conveying systems;

[0069] S4, repeat and cycle S3: repeat the surface modification treatment of the single crystal AlN powder of S3, the number of cycles is 20, the whole fluidization process duration is 130min, and a 2mm thick, uniformly distributed, stable performance alumina protective layer is formed on the surface of the single crystal AlN powder to obtain a single crystal AlN powder coated with an alumina protective layer.

[0070] The thickness of the aluminum oxide protective layer prepared in this embodiment is controlled at 2 nm. Figure 3 As shown, the hydrolysis resistance of the aluminum nitride single crystal powder after fluidization modification is significantly improved compared with that of the unmodified one. After the 80℃ / 72h hydrolysis test, the pH fluctuation value of the aluminum nitride single crystal powder after fluidization modification was 0.5-1, and the pH fluctuation value of the unmodified aluminum nitride single crystal powder was 2-6. The thermal conductivity of the fluidized aluminum nitride single crystal powder was improved by 10% compared with that of the unmodified one. The interfacial compatibility between the fluidized aluminum nitride single crystal powder and the organic matrix was improved. Under the same filling conditions, the filling limit of the unmodified one was 75vol%, and the filling limit of the modified one was increased to 85%.

[0071] Example 3

[0072] A method for modifying the surface of a single-crystal aluminum nitride powder by fluidization, the method comprising the following steps:

[0073] S1. Surface pretreatment of single crystal AlN powder: weigh 1 kg of AlN single crystal powder with a purity of 99.96% and a particle size of 5 μm, mix the AlN single crystal powder with anhydrous ethanol at a mass ratio of 1:3 to form an AlN suspension, place the suspension in an ultrasonic cleaning machine and start cleaning with ultrasonic and stirring, the ultrasonic temperature is 30°C, the ultrasonic time is 12 minutes, and then vacuum filtration is performed to obtain AlN filler wet powder;

[0074] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment at a temperature of 65°C for 2.5 hours to obtain a single crystal AlN powder with a clean surface; the single crystal AlN powder with a clean surface is spherical or quasi-spherical in shape, with a particle size of 5 μm and a water content of 99.96%;

[0075] S3, surface modification of single crystal AlN powder: the cleaned single crystal AlN powder in S2 is placed in a fluidized bed reactor; the heating device is turned on to control the required fluidization temperature of 200°C, at least one of trimethylaluminum, triacetylacetonate aluminum and aluminum chloride is introduced into the fluidized bed reactor by spraying and reacted under an inert atmosphere at a flow rate of 0.3 L / min for 6 min; at least one aluminum oxide precursor of trimethylaluminum, triacetylacetonate aluminum and aluminum chloride is introduced into the fluidized bed reactor through a gas input system. In the reactor, a surface covalent bonding reaction of the single crystal AlN powder is carried out in an environment of at least one inert gas selected from nitrogen and argon, at least one oxygen source selected from oxygen, ozone and water (H2O) is introduced into the fluidized bed reactor at a flow rate of 0.3 L / min for 6 min, the flow rate of the inert gas is 1 L / min, the fluidization temperature is 200° C., and the fluidization time is 320 min, to obtain a surface-modified single crystal AlN powder; wherein: the alumina precursor and the oxygen source are successively introduced into the fluidized bed reactor through different independent conveying systems;

[0076] S4, repeat and cycle S3: Repeat the surface modification treatment of the single crystal AlN powder in S3 for 25 cycles, forming an alumina protective layer of different thicknesses, uniform distribution and stable performance on the surface of the single crystal AlN powder, and obtaining a single crystal AlN powder coated with an alumina protective layer.

[0077] The thickness of the aluminum oxide protective layer prepared in this embodiment is controlled at 5 nm. Figure 4As shown, the hydrolysis resistance of the aluminum nitride single crystal powder after fluidization modification is significantly improved compared with that of the unmodified one. After the 80℃ / 72h hydrolysis test, the pH fluctuation value of the aluminum nitride single crystal powder after fluidization modification was 0.4-0.8, and the pH fluctuation value of the unmodified aluminum nitride single crystal powder was 2-6. The thermal conductivity of the fluidized aluminum nitride single crystal powder was improved by 15% compared with that of the unmodified one. The interfacial compatibility between the fluidized aluminum nitride single crystal powder and the organic matrix was improved. Under the same filling conditions, the filling limit of the unmodified one was 80vol%, and the filling limit of the modified one was increased to 90%.

[0078] Example 4

[0079] A method for modifying the surface of a single-crystal aluminum nitride powder by fluidization, the method comprising the following steps:

[0080] S1. Surface pretreatment of single crystal AlN powder: weigh 1 kg of AlN single crystal powder with a purity of 99.97% and a particle size of 7 μm, mix the AlN single crystal powder with anhydrous ethanol at a mass ratio of 1:2.5 to form an AlN suspension, place the suspension in an ultrasonic cleaning machine and start cleaning with ultrasonic and stirring, the ultrasonic temperature is 30°C, the ultrasonic time is 15 min, and then vacuum filtration is performed to obtain AlN filler wet powder;

[0081] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment, the drying temperature is 70°C, the time is 2 hours, and a single crystal AlN powder with a clean surface is obtained; the single crystal AlN powder with a clean surface is spherical or quasi-spherical in shape, with a particle size of 7 μm and a water content of 0.13%;

[0082] S3, surface modification of single crystal AlN powder: the cleaned single crystal AlN powder in S2 is placed in a fluidized bed reactor; the heating device is turned on to control the required fluidization temperature of 230°C, and at least one of trimethylaluminum, triacetylacetonate aluminum and aluminum chloride is introduced into the fluidized bed reactor by spraying and reacted under an inert atmosphere at a flow rate of 0.65 L / min for 4 min; and at least one of trimethylaluminum, triacetylacetonate aluminum and aluminum chloride is introduced into the fluidized bed reactor by a gas input system to react with aluminum oxide. The precursor is introduced into a fluidized bed reactor to carry out a surface covalent bonding reaction of the single crystal AlN powder in an environment of at least one inert gas selected from nitrogen and argon. At least one oxygen source selected from oxygen, ozone and water (H2O) is introduced into the fluidized bed reactor at a flow rate of 0.65 L / min, for 4 minutes, at a fluidizing temperature of 230°C, and for 350 minutes, to obtain a surface-modified single crystal AlN powder; wherein: the alumina precursor and the oxygen source are successively introduced into the fluidized bed reactor through different independent conveying systems;

[0083] S4, repeat and cycle S3: Repeat the surface modification treatment of the single crystal AlN powder in S3 for 40 cycles, forming an alumina protective layer of different thicknesses, uniform distribution and stable performance on the surface of the single crystal AlN powder, and obtaining a single crystal AlN powder coated with an alumina protective layer.

[0084] The thickness of the aluminum oxide protective layer prepared in this embodiment is controlled at 6 nm. Figure 5 As shown, the hydrolysis resistance of the aluminum nitride single crystal powder after fluidization modification is significantly improved compared with that of the unmodified one. After the 80℃ / 72h hydrolysis test, the pH fluctuation value of the aluminum nitride single crystal powder after fluidization modification was 0-0.4, and the pH fluctuation value of the unmodified aluminum nitride single crystal powder was 2-6. The thermal conductivity of the fluidized modified aluminum nitride single crystal powder is improved by 24% compared with that of the unmodified one. The interfacial compatibility between the fluidized modified aluminum nitride single crystal powder and the organic matrix is ​​improved. Under the same filling conditions, the filling limit of the unmodified one is 80vol%, and the filling limit of the modified one is increased to 92%.

[0085] Example 5

[0086] A method for modifying the surface of a single-crystal aluminum nitride powder by fluidization, the method comprising the following steps:

[0087] S1. Surface pretreatment of single crystal AlN powder: weigh 1 kg of AlN single crystal powder with a purity of 99.92% and a particle size of 9 μm, mix the AlN single crystal powder with anhydrous ethanol at a mass ratio of 1:4 to form an AlN suspension, place the suspension in an ultrasonic cleaning machine and start ultrasonic cleaning while stirring, the ultrasonic temperature is 32°C, the ultrasonic time is 12 min, and then vacuum filtration is performed to obtain AlN filler wet powder;

[0088] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment at a temperature of 72°C for 2 hours to obtain a single crystal AlN powder with a clean surface; the single crystal AlN powder with a clean surface is spherical or quasi-spherical in shape, with a particle size of 9 μm and a water content of 0.09%;

[0089] S3, surface modification of single crystal AlN powder: the cleaned single crystal AlN powder in S2 is placed in a fluidized bed reactor; the heating device is turned on to control the required fluidization temperature of 270°C, and at least one of trimethylaluminum, triacetylacetonate aluminum and aluminum chloride is introduced into the fluidized bed reactor by spraying and reacted under an inert atmosphere at a flow rate of 0.8 L / min for 5 min; then, at least one aluminum oxide precursor of trimethylaluminum, triacetylacetonate aluminum and aluminum chloride is introduced into the fluidized bed reactor through a gas input system. In the reactor, a surface covalent bonding reaction of a single crystal AlN powder is carried out in an environment of at least one inert gas selected from nitrogen and argon, at least one oxygen source selected from oxygen, ozone and water (H2O) is introduced into the fluidized bed reactor at a flow rate of 0.8 L / min for 5 min, the flow rate of the inert gas is 1.6 L / min, the fluidization temperature is 270°C, and the fluidization time is 380 min, to obtain a surface-modified single crystal AlN powder; wherein: an alumina precursor and an oxygen source are successively introduced into the fluidized bed reactor through different independent conveying systems;

[0090] S4, repeat and cycle S3: Repeat the surface modification treatment of the single crystal AlN powder in S3 for 35 cycles, forming an alumina protective layer of different thicknesses, uniform distribution and stable performance on the surface of the single crystal AlN powder, and obtaining a single crystal AlN powder coated with an alumina protective layer.

[0091] The thickness of the aluminum oxide protective layer prepared in this embodiment is controlled at 7nm. Figure 6 As shown, the hydrolysis resistance of the aluminum nitride single crystal powder after fluidization modification is significantly improved compared with that of the unmodified one. After the 80℃ / 72h hydrolysis test, the pH fluctuation value of the aluminum nitride single crystal powder after fluidization modification was 0.5-1, and the pH fluctuation value of the unmodified aluminum nitride single crystal powder was 2-6. The thermal conductivity of the fluidized modified aluminum nitride single crystal powder is improved by 28% compared with that of the unmodified one. The interfacial compatibility of the fluidized modified aluminum nitride single crystal powder and the organic matrix is ​​improved. Under the same filling conditions, the filling limit of the unmodified one is 80vol%, and the filling limit of the modified one is increased to 94%.

[0092] Example 6

[0093] A method for modifying the surface of a single-crystal aluminum nitride powder by fluidization, the method comprising the following steps:

[0094] S1. Surface pretreatment of single crystal AlN powder: weigh 1 kg of AlN single crystal powder with a purity of 99.98% and a particle size of 10 μm, mix the AlN single crystal powder with anhydrous ethanol at a mass ratio of 1:4.74 to form an AlN suspension, place the suspension in an ultrasonic cleaning machine and start ultrasonic cleaning while stirring, the ultrasonic temperature is 35°C, the ultrasonic time is 20 min, and then vacuum filtration is performed to obtain AlN filler wet powder;

[0095] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment at a temperature of 75°C for 2 hours to obtain a single crystal AlN powder with a clean surface; the single crystal AlN powder with a clean surface is spherical or quasi-spherical in shape, with a particle size of 10 μm and a water content of 0.05%;

[0096] S3, surface modification of single crystal AlN powder: the cleaned single crystal AlN powder in S2 is placed in a fluidized bed reactor; the heating device is turned on to control the required fluidization temperature of 300°C, at least one of trimethylaluminum, triacetylacetonate aluminum and aluminum chloride is introduced into the fluidized bed reactor by spraying and reacted under an inert atmosphere at a flow rate of 1 L / min for 6 min; at least one aluminum oxide precursor of trimethylaluminum, triacetylacetonate aluminum and aluminum chloride is introduced into the fluidized bed reactor through a gas input system. In the reactor, a surface covalent bonding reaction of the single crystal AlN powder is carried out in an environment of at least one inert gas selected from nitrogen and argon, at least one oxygen source selected from oxygen, ozone and water (H2O) is introduced into the fluidized bed reactor at a flow rate of 1 L / min for 6 min, the flow rate of the inert gas is 2 L / min, the fluidization temperature is 300°C, and the fluidization time is 500 min, to obtain a surface-modified single crystal AlN powder; wherein: the alumina precursor and the oxygen source are successively introduced into the fluidized bed reactor through different independent conveying systems;

[0097] S4, repeat and cycle S3: Repeat the surface modification treatment of the single crystal AlN powder in S3 for 40 cycles, forming an alumina protective layer of different thicknesses, uniform distribution and stable performance on the surface of the single crystal AlN powder, and obtaining a single crystal AlN powder coated with an alumina protective layer.

[0098] The thickness of the aluminum oxide protective layer prepared in this embodiment is controlled at 8 nm. Figure 7As shown, the hydrolysis resistance of the aluminum nitride single crystal powder after fluidization modification is significantly improved compared with that of the unmodified one. After the 80℃ / 72h hydrolysis test, the pH fluctuation value of the aluminum nitride single crystal powder after fluidization modification was 0-0.3, and the pH fluctuation value of the unmodified aluminum nitride single crystal powder was 2-6. The thermal conductivity of the fluidized aluminum nitride single crystal powder was improved by 30% compared with that of the unmodified one. The interfacial compatibility between the fluidized aluminum nitride single crystal powder and the organic matrix was improved. Under the same filling conditions, the filling limit of the unmodified one was 80vol%, and the filling limit of the modified one was increased to 95%.

[0099] The above scheme, the present invention proposes a fluidized modification method for the surface of single-crystal aluminum nitride powder, which can solve the problem that the surface of single-crystal AlN powder in the prior art is generally modified to prepare a hydrophobic coating to resist hydrolysis, but does not consider that the modification is to enhance the mechanical strength of the aluminum nitride filler, improve its thermal conductivity, filling limit, compression resistance, tensile strength and bending resistance, and does not consider the technical problem that the thickness uniformity, thickness control, durability, stability and other properties of the modified coating are difficult to control.

[0100] The present invention can achieve uniform coating and thickness control on the surface of single crystal AlN powder through fluidization modification technology, ensuring that each particle can obtain an aluminum oxide protective layer with uniform thickness uniformly distributed by aluminum oxide particles, thereby improving the overall performance of the material.

[0101] The fluidized modification technology of the present invention can ensure the formation of a strong chemical bond between the aluminum oxide layer and the single crystal AlN powder by covalent bonding, which not only improves the adhesion between the two, but also improves the overall durability and performance stability of the filler.

[0102] The aluminum oxide layer with uniform thickness and uniform particle distribution of the present invention can improve the thermal stability and chemical stability of single crystal AlN powder under high temperature conditions, so that it performs better in extreme environments.

[0103] The present invention can flexibly and accurately control the thickness and properties of the aluminum oxide layer by adjusting the process parameters in the fluidized modification process to meet different industrial application requirements.

[0104] The present invention obtains modified AlN single crystal powder by modifying the surface of single crystal AlN powder, which can enhance the hydrolysis resistance, thermal conductivity, interface compatibility and other properties of aluminum nitride single crystal powder, broadens the application range and improves the use value.

[0105] In summary, compared with other traditional methods, the method of the present invention can achieve uniform coating and thickness control on the surface of single crystal AlN powder through fluidized modification technology, and can obtain modified single crystal AlN powder that can enhance the mechanical strength, compressive strength, tensile strength and flexural strength of aluminum nitride filler; the method is simple and easy to operate, reduces dependence on harmful solvents, is green and environmentally friendly, has low cost and high efficiency, and is conducive to large-scale industrial production and promotion.

[0106] It should be understood that the term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship, but it may also indicate an "and / or" relationship. Please refer to the context for specific understanding.

[0107] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, at least one of a, b, or c can mean: a, b, c, ab, ac, bc, or abc, where a, b, and c can be single or multiple.

[0108] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0109] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for fluidizing the surface of single-crystal aluminum nitride powder, characterized in that: The single crystal aluminum nitride powder surface fluidization modification method comprises the following steps: S1. Surface pretreatment of single crystal AlN powder: weigh an appropriate amount of high-purity single crystal AlN powder, mix the single crystal AlN powder with anhydrous ethanol to prepare an AlN suspension, place the suspension in an ultrasonic cleaning machine and start a cleaning process while ultrasonicating and stirring, and then perform vacuum filtration to obtain AlN filler wet powder; S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment to obtain a single crystal AlN powder with a clean surface; S3, surface modification of single crystal AlN powder: placing the cleaned single crystal AlN powder in S2 in a fluidized bed reactor, turning on a heating device to control the required fluidization temperature, introducing an alumina precursor into the fluidized bed reactor by spraying and reacting under an inert atmosphere, and then introducing an oxygen source into the fluidized bed reactor through a gas input system to carry out a surface covalent bonding reaction of the single crystal AlN powder under an inert atmosphere, thereby obtaining surface-modified single crystal AlN powder; S4, repeat and cycle S3: repeat the surface modification treatment of S3 on the surface modified single crystal AlN powder of S3, forming an alumina protective layer with different thicknesses, uniform distribution and stable performance on the surface of the single crystal AlN powder, and obtaining a single crystal AlN powder coated with an alumina protective layer.

2. The method for surface fluidization modification of single crystal aluminum nitride powder according to claim 1, characterized in that: The particle size of single crystal AlN powder in S1 is 1-20μm; the purity is 99.90-99.99%.

3. The method for surface fluidization modification of single crystal aluminum nitride powder according to claim 1, characterized in that: The mass ratio of single crystal AlN powder to anhydrous ethanol in S1 is 1:(1.58-4.74).

4. The method for surface fluidization modification of single crystal aluminum nitride powder according to claim 1, characterized in that: The ultrasonic parameters of the cleaning process in S1 are set as follows: ultrasonic temperature 25-35°C, ultrasonic time 10-20min.

5. The method for surface fluidization modification of single crystal aluminum nitride powder according to claim 1, characterized in that: The drying temperature in S2 is 50-75°C for 2-4 hours. The single crystal AlN powder with clean surface is spherical or quasi-spherical in shape, with a particle size of 1-20 μm and a water content of 0.05-0.2%.

6. The method for surface fluidization modification of single crystal aluminum nitride powder according to claim 1, characterized in that: The aluminum oxide precursor in S3 is at least one of trimethylaluminum, aluminum triacetylacetonate and aluminum chloride, and the flow rate of the aluminum oxide precursor is 0.3-1 L / min, and the time is 3-6 min.

7. The method for surface fluidization modification of single crystal aluminum nitride powder according to claim 1, characterized in that: The oxygen source in S3 is at least one of oxygen, ozone and water (H2O), and the oxygen source flow rate is 0.3-1L / min, and the time is 3-6min.

8. The method for surface fluidization modification of single crystal aluminum nitride powder according to claim 1, characterized in that: The inert atmosphere in S3 is at least one of nitrogen and argon. The inert gas is introduced from the beginning to the end of fluidization, and the flow rate of the inert gas is 0.2-2L / min. The fluidization treatment temperature is 120-300°C, and the fluidization time is 80-500min.

9. The method for surface fluidization modification of single crystal aluminum nitride powder according to claim 1, characterized in that: In S3, the alumina precursor and the oxygen source enter the fluidized bed reactor successively through different independent delivery systems.

10. The method for surface fluidization modification of single crystal aluminum nitride powder according to claim 1, characterized in that: The number of cycles mentioned in S4 is 10-40, and the thickness of the aluminum oxide protective layer is controlled at 2-8nm; after the 80℃ / 72h hydrolysis test, the pH fluctuation value of the aluminum nitride single crystal powder after fluidization modification is 0-1, and the pH fluctuation value of the unmodified aluminum nitride single crystal powder is 2-6; The thermal conductivity of fluidized modified aluminum nitride single crystal powder is improved by 10-30% compared with unmodified one; The interfacial compatibility between the fluidized modified aluminum nitride single crystal powder and the organic matrix is ​​improved. Under the same filling conditions, the filling limit of the unmodified powder is 75-80 vol%, and the filling limit of the modified powder is increased to 88-95 vol%.

Citation Information

Patent Citations

  • Hydrolysis-resistant modification method of aluminum nitride powder

    CN112250047A

  • Aluminum nitride powder and modification preparation method thereof

    CN112919432A

  • Preparation method of high-temperature anti-oxidation aluminum nitride and aluminum oxide heat-conducting filler

    CN113772638A

  • Preparation method of surface-coated modified nickel cobalt lithium manganate ternary positive electrode material

    CN112382739A

  • Preparation method of high-purity aluminum nitride

    CN114105110A